2020
DOI: 10.1155/2020/8884797
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Car-Following Behaviour of Turning Movements at Intersections with Consideration of Turning Radius

Abstract: In order to deeply analyze and describe the characteristics of car-following behaviour of turning vehicles at intersections, the features and application conditions of classic car-following models were analyzed firstly. And then, through analysing the relationship between the maximum velocity of car-following vehicles and the turning radius of intersection, the differences in key variables between turning and straight car-following behaviour were identified. On the basis of Optimal Velocity (OV) model, a Turni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
3
0
4
Order By: Relevance
“…Turning is a very common situation when driving a vehicle. 30 In this section, the dynamic response in turning situations is studied. The test vehicle was driven on B roads and decelerated from 40 km/h, 50 km/h, 60 km/h, 70 km/h, and 80 km/h to 30 km/h while executing a continuous curve.…”
Section: Resultsmentioning
confidence: 99%
“…Turning is a very common situation when driving a vehicle. 30 In this section, the dynamic response in turning situations is studied. The test vehicle was driven on B roads and decelerated from 40 km/h, 50 km/h, 60 km/h, 70 km/h, and 80 km/h to 30 km/h while executing a continuous curve.…”
Section: Resultsmentioning
confidence: 99%
“…Both the frequency and severity of crashes show an increased trend [17]. In addition, rural SV crashes occurring between 6:00 p.m. and 12:00 p.m. are unlikely to result in serious injury [29,31]. The same research suggested that serious crashes were more likely to occur during the winter season.…”
Section: Temporal Characteristicsmentioning
confidence: 95%
“…Several traffic characteristics, such as speed limit and traffic volume, were demonstrated to be significantly correlated with rural SV crash severity [29,30]. In detail, crashes occurring on roadways with speed limits below 35 mph or AADT (Annual Average Daily Traffic) above 5000 were more likely to result in less serious injury outcomes due to a safe speed being maintained under car-following conditions [31].…”
Section: Environmental Characteristicsmentioning
confidence: 99%
“…Розробці математичного апарату, що описує круговий рух транспортного засобу по горизонтальній дорозі з описом поворотів, присвячена робота [5]. Поведінка слідування автомобіля і зміна смуги руху в транспортному потоці розкрита в роботі [6], розробка моделі слідування за автомобілями, що повертають транспортні засоби на перехрестях, наведена в [7]. Моделі прогнозування руху автомобіля на перехрестях на основі моделі намірів повороту та попередніх траєкторій розглянуті в [8].…”
Section: вступunclassified
“…, залежність (7) За попереднім аналізом входження в поворот по кривій, що описується рівнянням гіперболічного косинуса, є більш сприятливим, порівняно з іншими варіантами, оскільки поєднує більшу плавність зміни кривини в зоні спряження із достатнім радіусом кривини для забезпечення стійкості автомобіля від дії відцентрових сил. За результатами досліджень напрацьовані рекомендації щодо раціональної траєкторії входження в поворот та вибору швидкісного режиму, який забезпечує стійкість та керованість автомобіля при проходженні повороту для різних видів перехрестя, зокрема і під непрямими кутами.…”
Section: результати дослідженняunclassified